2011
DOI: 10.1111/j.1467-8683.2011.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Institutional Investors and Foreign Blockholdings in France: The Evolution of an Institutionally Hybrid Economy

Abstract: Manuscript Type: EmpiricalResearch Question/Issue: What are some of the key factors that facilitate/constrain the acquisition of concentrated equity stakes (>5 per cent) by Anglo-American institutional investors in French companies?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 128 publications
1
18
0
Order By: Relevance
“…In general, foreign ownership of French firms increased significantly, from 10 percent of total equity in 1985 to 35 percent in 1997 (Clift, ). According to Goyer and Jung (: 563), France represents an institutionally “hybrid” economy, the largest representative of institutionally hybrid, developed, economies. This type of economy is “highly interesting for the analysis of the strategy of international investment by UK/US‐based institutional investors,” given that its “hybrid” character was instrumental in attracting Anglo‐American funds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, foreign ownership of French firms increased significantly, from 10 percent of total equity in 1985 to 35 percent in 1997 (Clift, ). According to Goyer and Jung (: 563), France represents an institutionally “hybrid” economy, the largest representative of institutionally hybrid, developed, economies. This type of economy is “highly interesting for the analysis of the strategy of international investment by UK/US‐based institutional investors,” given that its “hybrid” character was instrumental in attracting Anglo‐American funds.…”
Section: Methodsmentioning
confidence: 99%
“…A possible further differentiation of Anglo‐American institutional investors would be one based on their temporal orientation, i.e., long term vs. short term (see, e.g., Goyer & Jung, ). For instance, Goyer and Jung () proceed to such differentiation with the use of a dichotomous variable based on the median turnover rate of investors. In our study, we were unable to systematically differentiate the Anglo‐American institutional investor category based on a categorization of their activity as (exclusively) long‐term‐oriented vs. short‐term‐oriented.…”
mentioning
confidence: 99%
“…In multinational firm context, it is hard for foreign shareholders to monitor managerial decision because of complexity of corporate structure with many foreign subsidiaries across country (S. . Not only foreign manager have adaptation difficulty in domestic environment, but domestic manager as well have adaptation difficulty in firm where foreign shareholders have brought foreign atmosphere in some business activities, for example, research by Goyer & Jung (2011) found that social capital domestic CEO could reduce foreign ownership because of foreign atmosphere in some business activities. Those…”
Section: Discussionmentioning
confidence: 99%
“…Not only foreign manager have adaptation difficulty in domestic environment, but domestic manager as well have adaptation difficulty in firm where foreign shareholders have brought foreign atmosphere in some business activities. Goyer & Jung (2011) found that social capital domestic CEO could reduce foreign ownership.…”
Section: Corporate Governance Foreign Ownership and Firm Valuementioning
confidence: 99%
“…Institutions, like codes, are important but do not strictly determine behavior, even when they reduce the range of available strategic options. Strategic choice remains possible as a firm's stakeholders constitute sub‐groups with different interests and incentives that affect how they operate in an institutional framework (Aguilera & Jackson, ; Goyer & Jung, ). In the UK, this is even more so because the institutions are self‐regulatory.…”
Section: A Political Perspective On Business Elites and Institutionalmentioning
confidence: 99%